The Influence of E-Marketing on Achieving Organizational Excellence: A Survey Study of Private Bank Branches in Damascus (TANMIYAT AL-RAFIDAIN, 2026)
This study addresses a crucial issue in the contemporary banking sector: the role of e-marketing in achieving organizational excellence as a key driver of competitive advantage.  The research focused specifically on branches of private banks operating in Damascus, aiming to analyze how transforming digital tools into "internal differentiation capabilities" can contribute to a bank's superiority over its competitors and the achievement of a competitive advantage within a changing economic and technological environment. The study employed a descriptive-analytical (quantitative) methodology, collecting data through a questionnaire distributed to a sample of 70 administrative staff members in the targeted banks. The data were then statistically analyzed using SPSS to test hypotheses regarding the impact of digital channels on competitive advantage. The study concluded that adopting e-marketing methods is a fundamental pillar for achieving organizational excellence, which positively impacts competitive advantage. The statistical results showed that marketing through the official website has a statistically significant impact on enhancing competitive advantage, with the largest effect size (coefficient of determination) of 31%. Marketing through social media platforms also has a statistically significant impact on enhancing competitive advantage, with a contribution of 24%. These findings confirm that excellence in managing these digital platforms transforms them from mere technological tools into a tangible "external competitive advantage. Based on these results, the study recommends intensifying efforts and achieving excellence in social media marketing, with a focus on measuring the true impact of promotional campaigns to ensure effective performance.
Keywords: E-marketing; organizational excellence; competitive advantage; private banks